(untitled) (Libellarium: journal for research in the field of information and related sciences, 2013)
Luciano Floridi is an Italian philosopher with an Anglo-Saxon career, who started a new philosophical discipline, the philosophy of information (Floridi 2002). As opposed to most authors who deal with this subject, Floridi, in his rich opus, treats information as a broader concept. However, this paper will treat information neither as a social and ethical phenomenon, nor as information and communication technologies. The aim of the paper is to examine information as a subject of philosophical investigation. The paper gives an overview of and a comment on the theory of semantic information that Floridi presented in two core articles: Semantic Conceptions of Information (2011) and Outline of a Theory of Strongly Semantic Information (2004). The first text gives an overview of ideas that form a framework for the philosophical analysis of information and presents the main theses of Floridi’s theory of semantic information. The second text is a step away from the philosophical towards the scientific theory by using situational logic as a basis for quantification (measurement) of two dimensions of semantic information: inaccuracy and vacuity.